Family participation in playgrounds as an indicator of quality. Systematic mapping study - López-Perea, Eva; Diez-Ojeda, María; Ollora-Triana, Natalia; Alonso-Alcalde, Nuria (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this research, an analysis of the regional and local regulations and protocols of the toy libraries belonging to the autonomous community of Castilla y León (Spain) is carried out during the years 2017-2022. Part of the systematic mapping design of regulations with the following inclusion criterion “localities with more than 5000 inhabitants of the Castilian-Leonese community” because it is understood that these have economic resources to maintain these socio-community services over time. The documents between the years 2017 and 2022 are studied with the intention of analyzing the evolution of the toy libraries in Castilla y León.